MERDEKA BELAJAR-KAMPUS MERDEKA IN DEVELOPING BUSINESS ENTREPRENEURS - Sutangsa (International Journal of Social Science, 2021)
Merdeka Belajar-Kampus Merdeka is an innovative breakthrough program in building human resources full of creativity and innovation with the aim of being able to compete in the global arena. This breakthrough program policy is seen in the perspective of fostering an entrepreneurial spirit aimed at preparing students to become strong graduates, relevant to the needs of the times, and ready to become leaders with a high spirit of nationalism. Students who are currently studying at tertiary institutions, must be prepared to become true learners who are skilled, flexible and resilient (agile learners). The keywords in entrepreneurship are creativity and innovation. Emphasis on these two aspects can be seen from the learning process. Increasing and even changing the mental structure of students is expected to be oriented to innovation and creativity that have economic value. Entrepreneurial success is a part of the process of creativity and innovation, this is in line with what was stated by Schumpeter (1934) about the destruction of value in an established market structure. Entrepreneurs offer value that can change the structure of an established market. These values         are formulated based on creativity and innovation.